Apomictic development during different flower development stages in Crataegus tanacetifolia (Lam.) Pers., endemic to Turkey - ÇETİNBAŞ GENÇ, ASLIHAN (My University, 2021)
In this study, aposporic apomictic development and its relation to the different flower development stages were investigated by light and fluorescence microscopy in Crataegus tanacetifolia (Lam.) Pers. (Rosaceae). At pre-anthesis stage, aposporic initial cell differentiated at the somatic nucellus tissue shortly after the megaspore mother cell formation. The volume of aposporic initial cell increased during the generation of dyad and megaspore tetrad respectively by regular meiosis. At this stage, linear megaspore tetrad and vacuolated aposporic initial cell were located side by side into the same ovule. At anthesis stage, before pollination, four nucleated aposporic embryo sac was formed while sexual development came to end by atrophy of megaspores completely. At this stage, atrophied megaspores and two nucleated aposporic embryo sac were located side by side into the same ovule. At post-anthesis stage, pollination still had not begun and ovule contained only eight nucleated aposporic embryo sac. Mature aposporic embryo sac was composed of two synergid cells and one egg cell on the micropylar side, three antipodal cells on the chalazal side and a central cell with two polar nuclei in the middle of the sac. The absence of filiform apparatus in the synergid cells was quite remarkable. No callose accumulation around the aposporic initial cell was observed in any development stage. Pollination started shortly after the proembryo formation. Embryo and endosperm developed without fertilization due to the problems encountered in reaching pollen tubes to the ovary.